Leadership Effectiveness: A Contingency Approach - Justis, Robert T. (Academy of Management Journal, 1975)
The article discusses leadership effectiveness. The theoretical and empirical research of F.E. Fiedler on ?contingencies? model has provided greater understanding and insight in the area of leadership effectiveness. The three primary functions which Fiedler's theory is based on are discussed. He focuses on the relationship between positional power, the nature of the subordinate's task and the nature of the interpersonal relationship or the leader-member relation of the leader and the follower. Additional research has shown that the level of leadership effectiveness is strongly influenced by the perceived task competency of the leader and the reward dependency of the subordinate upon the leader.